Effects of wearable therapies on jump performance in sport horses - Schmidt, Therese E.; Gleason, Claire B.; Samaniego, Mercedez R.; White, Robin R. (Frontiers in Veterinary Science, 2023)
Failure to properly prepare the equine athlete for exercise and support post-exercise recovery is a contributing factor to physical breakdown and lameness. Equine physiotherapy was not introduced until the early twentieth century and has since evolved to allow for wearable therapies such as therapeutic boots to be accessible to a broad spectrum of equestrians. The purpose of this study was to evaluate the effects of ceramic boots, boots combining vibration and cryotherapy, and boots containing tourmaline on the performance of sport horses during jumping as well as to examine biological changes in vital signs in response to treatment. Eight healthy horses received the 3 therapeutic boot treatments or a control (no boot) in a Latin square experiment for a period of 5 days each. Horses performed approximately 10 min of exercise through a jump chute for the 5 consecutive days and. Jjump performance parameters were recorded during each exercise session and blood samples were collected on days 1, 3, and 5 of each period. Therapeutics were applied in the morning prior to exercise per the manufacturer's recommendation and were removed only for exercise. Blood serum was analyzed for concentrations of C reactive protein (CRP), basic fibroblast growth factor (bFGF), and tenascin C (TN-C). In a Bayesian network analysis, changes in vital signs (heart rate, respiration, and temperature) and serum biomarkers were driven by individual animal, rather than boot treatment. Jump performance was influenced by boot treatment, physiological measurements, and individual animal. Therapeutic boots were associated with changes in conditional probabilities of numerous performance outcomes. This study indicates the use of wearable therapies may result in improved performance outcomes of sport horses in jumping exercises.